Perlindungan Hukum Terhadap Justice Collaborator di Indonesia (Analisa Putusan Nomor : 48/Pid.Sus/TPK/2016/PN.Jkt Pst) - Taberima, Rylke Marviano; Hehanussa, Deassy Jacomina Anthoneta; Adam, Sherly (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Corruption harms the country's finances and the socio-economy of society. Corruption tends to be committed by more than one person. Corruption crimes that have been caught by the Corruption Eradication Commission (KPK) have obstacles to revealing and detaining parties who have committed corruption crimes due to a lack of information or data. Then came the idea of the Justice Collaborator (JC), which was first known in America in the 1970s, namely cooperation to reveal the main mastermind of the corruption crime with the convict of corruption. The key role of a justice collaborator is to uncover a crime or the occurrence of a crime, so that the return of assets from the results of a crime can be achieved to the state. Purposes of the Research: Analyzing the urgency of Justice Collaborator corruption in Indonesia. Methods of the Research: The research method used is juridical-normative research. Data sources include primary data and secondary data. Data collection techniques through the study of documentation and data analysis used Qualitative Analysis. The problem approaches used in this research are statute, conceptual, and case approaches. Results of the Research: The results research the urgency or existence of a Justice Collaborator at the stage of Investigation in corruption in Indonesia is essentially to assist law enforcement officers in finding and finding facts related to crimes including corruption, which is difficult to disclose because the perpetrators of corruption more than one. The issue of legal protection for Justice Collaborator, LPSK law regulates the protection of witnesses including Justice Collaborator. Although in reality the process of determining the status of Justice Collaborator must be based on the submission of which institution handles the case. This is because the position of LPSK is only a sub-supporter in the criminal justice system so the recommendations of the Justice Collaborator LPSK can be obeyed or not obeyed.